Cholesterol treatment with statins: Who is left out and who makes it to goal? - Winters Paul; Tancredi Daniel; Franks Peter; Fiscella Kevin (BMC, 2010)
Abstract Background Whether patient socio-demographic characteristics (age, sex, race/ethnicity, income, and education) are independently associated with failure to receive indicated statin therapy and/or to achieve low density lipoprotein cholesterol (LDL-C) therapy goals are not known. We examined socio-demographic factors associated with a) eligibility for statin therapy among those not on statins, and b) achievement of statin therapy goals. Methods Adults (21-79 years) participating in the United States (US) National Health and Nutrition Examination Surveys, 1999-2006 were studied. Statin eligibility and achievement of target LDL-C was assessed using the US Third Adult Treatment Panel (ATP III) on Treatment of High Cholesterol guidelines. Results Among 6,043 participants not taking statins, 10.4% were eligible. Adjusted predictors of statin eligibility among statin non-users were being older, male, poorer, and less educated. Hispanics were less likely to be eligible but not using statins, an effect that became non-significant with adjustment for language usually spoken at home. Among 537 persons taking statins, 81% were at LDL-C goal. Adjusted predictors of goal failure among statin users were being male and poorer. These risks were not attenuated by adjustment for healthcare access or utilization. Conclusion Among person's not taking statins, the socio-economically disadvantaged are more likely to be eligible and among those on statins, the socio-economically disadvantaged are less likely to achieve statin treatment goals. Further study is needed to identify specific amenable patient and/or physician factors that contribute to these disparities.